Congratulatory remarks for JEECAR's 5th Anniversary - Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
Dear JEECAR Editorial Board and Contributors: On the occasion of the Journal’s 5th Anniversary, please accept my best wishes. In a short period, you brought the journal to be recognized by the SCOPUS, CABELL, EBSCO, Ulrich, and other academic databases. The Journal advances scholarship knowledge and actively contributes to the better understanding of the global society and economy.